BREAKING GENDER STEREOTYPES: HOW INTERACTING WITH STEM PROFESSIONALS CHANGED FEMALE STUDENTS' PERCEPTIONS - Donmez, Ismail (Sci Methodical Ctr-Sci Educologica, 2023)
Various studies have reported that students have limited, stereotypical perceptions of STEM fields. However, few studies have attempted to evaluate interventions undertaken with the aim of changing female student's perceptions of STEM professions. This research aimed to examine the changes in mental images among female students as a result of interacting with STEM professionals in a STEM camp. The Draw-a-Scientist Test was revised, and female students were asked to draw and describe STEM professionals at work before and after attending STEM camp. The participating students attended workshops and career talks given by STEM professionals. The findings showed that the perceptions of the participating female students regarding gender images of STEM professionals changed. After the STEM camp, it was also observed that knowledge about STEM professionals and the content of their work had increased. The studied intervention program for female students positively contributed to changes in the students' mental images of STEM professionals. Therefore, it is recommended that female students interact with professionals working in STEM fields to change their perceptions of those fields.
Keywords: female students; gender stereotypes; human images in STEM; role models; STEM